ANALISIS GAYA MENGAJAR GURU DALAM MEMOTIVASI UNTUK BELAJAR BAHASA INDONESIA DI KELAS V SDN BANJARPANJI KABUPATEN SIDOARJO - Sulistia, Nadia Eka; Pratikno, Ahmad Sudi (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
There are still many students who have difficulty understanding, completing, and lack interest and motivation in Indonesian lessons taught by teachers, so that Indonesian learning outcomes are not optimal. These factors can arise from the teacher's teaching style, the use of learning methods, the implementation of learning models, and so on. This research aims to find out how the teacher's teaching style motivates students in Indonesian language learning in class V SDN Banjarpanji. This research is a type of qualitative research with a descriptive approach. The data collection techniques used were observation, interview, and documentation. While the data instrument is an observation sheet,. Based on the description of the data, it states that the teacher's teaching style in motivating students in learning Indonesian in class V SDN Banjarpanji is the delivery of material in detail and using clear language, applying question and answer methods and lectures, the teaching style used is personalization and interactional, conducting questions and answers, giving rewards or praise, evaluations in the form of homework or LKS assignments. Supporting factors experienced by teachers include the availability of complete infrastructure. The inhibitory factor is student enthusiasm and is only guided by the package book, it can be concluded that the teacher's teaching style given to students is able to motivate students in learning mathematics in class V SDN Banjarpanji.